Assessment instrument for practicum skills in Trimyristin separation for undergraduate students - Naseer Ahmed; Senam Senam; Antuni Wiyarsi (Faculty of Mathematics and Natural Sciences, Universitas Negeri Yogyakarta, 2019)
Assessment of practicum plays an essential role in gaining knowledge and skill. Because practical work is an essential component of science courses, there were need to develop new instruments to examine practicum skill. To gain the purpose, Research and Development method used, Borg and Gall's model was adopted in this research. Observation sheets were used to obtain data. The qualitative data analysis technique was used to make coding. The data were described using descriptive statistics. It was used to determine the ability of students to practice in general, purposive sampling technique used for data collection. Products of practical’s skills assessment contain four aspects, fifteen indicators, and four criteria. The product was validated by two expert judges, shortcomings and grammatical mistakes were revised. In the separation of trimyristin, mostly student practicum skill was